Edukasi Kesehatan Pada Lansia Hipertensi Di Wilayah Kerja Puskesmas Jembatan Kecil Rt 11 Kota Bengkulu - Elis Novera Ilma Reza; Desy Tri; Adjie Adjie; Andika Junaldi; Devi Ramadhona; Meychania Agyathien; Mariza Afrianti; Ravika Ramlis; Desi Aulia Umami (Utami Publisher, 2025)
Hypertension remains a global target, to reduce hypertension sufferers in 2010 to 2030 (WHO, 2021). Hypertension is often referred to as high blood pressure is a condition where there is an increase in blood pressure in the abdominal arteries that occurs repeatedly with an increase in systolic pressure of more than or equal to 140 mmHg and an increase in diastolic pressure of more than or equal to 90 mmHg (Sriyanti, 2022). One of the treatments for hypertension. This KKN-T activity is a form of community service that aims to increase the knowledge, awareness and behavior of the RT 11 community of Jembatan Kecil Village about the Risk of Hypertension. This activity is in accordance with the priority program in accelerating efforts to prevent and treat hypertension which is also emphasized in the UPTD Jembatan Kecil Health Center program. The program is implemented through educational methods, blood pressure checks carried out in RT 11, Jembatan Kecil Village, Singaran Pati District, Bengkulu City with the target community, the elderly, hypertension sufferers and cadres totaling 20 people. The community has received information about the causes, signs and symptoms, and prevention. The results of this activity indicate an increase in public knowledge about hypertension and prevention. This helps the community better understand hypertension and take appropriate preventive measures. It is hoped that the community will implement preventive measures to manage hypertension in Jalan Gedang Village.